CONSTRUCTION AND VALIDATION OF A CLINICAL SCENARIO AND CHECKLIST FOR ASSESSING CARDIOPULMONARY RESUSCITATION SKILLS - Dias, Amanda Aparecida; Costa, Yule Caroline Nunes da; Tony, Ana Carolina Carraro; Alvim, André Luiz Silva; Prado, Roberta Teixeira; Santos, Kelli Borges dos; Carbogim, Fábio da Costa (Cogitare Enfermagem, 2023)
Objectives: to build and validate a simulated scenario and checklist to assess skills in the care of hemodynamically unstable patients with evolution to Cardiorespiratory Arrest, and to test applicability to the target population, assessing skills and satisfaction/self-confidence with learning. Method: methodological study carried out in three stages (development of the scenario and checklist, validation by judges and pilot test) between April 2020 and September 2021, in the state of Minas Gerais, Brazil. Fourteen judges and 24 nursing students participated. Results: the scenario and checklist achieved a Content Validity Coefficient greater than 90. The skills were adequately developed, with a mean of 4.71 ± 0.24 on the satisfaction-self-confidence scale, and 4.83 ± 0.25 for simulation design. Conclusion: The scenario may contribute to improving educational activities in undergraduate and health education and subsidize future studies to increase the quality of care and assistance to hemodynamically unstable patients with evolution to cardiac arrest.